Una contribución de la psicología ambiental a la discusión de aspectos comportamentales de la evaluación post-ocupación - Elali, Gleice Azambuja (2006)
The understanding of human behavior in the environment is one of the main contributions of environmental psychology to the post-occupancy evaluation (POE), especially in terms of developing observation techniques, such as behavioral traces, behavioral mapping, and behavior-setting analysis. Based on this premise, this paper brings an overview of this field and discusses its potential applications in architectonic and urbanistic proposals.